The Long Way of Knowledge Society (Informatică economică, 2007)
I think, therefore I am. Our ancestors said Cogito, ergo sum, in a Latin form of Rene Descartes' expression "Je pense, donc je suis", in Discourse on Method (1637). The same did Thomas Davenport, when gave his book the title Thinking for a living. Probably he didn't prefer the direct form in English of the above mentioned expression: "I think, therefore I am", but one that in essence is more poetical and more anchored in the reality of the third millennium's early days, in the way that only thinking we can exist. The title is also a commercial one, because the previous ten books also basically referred to knowing or knowledge. They used the research done in the following fields: knowledge management, process management and innovation. The opening of his last book, a best seller of 2005, is also interesting. The author gives the first chapter the title 'What's a Knowledge Worker, Anyway?". We could draw the conclusion that after so much effort, including a publishing one, the author remains with the doubt on the terminology so much used at the end of the 2nd millennium and the beginning of the 3rd one or leaves an open way to the next volumes. It is not by chance that there are voices that say he might be the next Peter Drucker. The last one said that the future society would be the knowledge society (see also Managing in the Next Society, 2002).